Insights into the pre-initiation events of bacteriophage phi 6 RNA-dependent RNA polymerase: towards the assembly of a productive binary complex. - Sarin, L; Poranen, M; Lehti, N; Ravantti, J; Koivunen, MR; Aalto, A; van Dijk, A; Stuart, D; Grimes, J; Bamford, D (2009)
The RNA-dependent RNA polymerase (RdRP) of double-stranded RNA (dsRNA) viruses performs both RNA replication and transcription. In order to initiate RNA polymerization, viral RdRPs must be able to interact with the incoming 3' terminus of the template and position it, so that a productive binary complex is formed. Structural studies have revealed that RdRPs of dsRNA viruses that lack helicases have electrostatically charged areas on the polymerase surface, which might facilitate such interactions. In this study, structure-based mutagenesis, enzymatic assays and molecular mapping of bacteriophage phi 6 RdRP and its RNA were used to elucidate the roles of the negatively charged plough area on the polymerase surface, of the rim of the template tunnel and of the template specificity pocket that is key in the formation of the productive RNA-polymerase binary complex. The positively charged rim of the template tunnel has a significant role in the engagement of highly structured ssRNA molecules, whereas specific interactions further down in the template tunnel promote ssRNA entry to the catalytic site. Hence, we show that by aiding the formation of a stable binary complex with optimized RNA templates, the overall polymerization activity of the phi 6 RdRP can be greatly enhanced.